(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
An important stage in the student’s educational activity is the stage of primary education. It is the task of every pedagogue and psychologist to form positive relationships, high positive and human characteristics in the student of this period. Therefore, a number of recommendations for the implementation of this urgent task are presented in this article